Towards hydroxylated nylon 6: linear and cyclic oligomers from a protected 6-amino-6-deoxy-D-galactonate - a novel class of carbopeptoid-cyclodextrin (CPCD) - Mayes, B; Stetz, R; Watterson, M; Edwards, A; Ansell, C; Tranter, G; Fleet, G (2004)
Circular dichroism studies on a series of linear oligomers derived from a protected 6-amino-6-deoxy-D-galactonate (an ε-amino acid) indicated a predisposition to form a rigid structure in solution, which is comparable to a β-sheet composed of L-amino acids; in contrast, a diastereomeric allonate series provided no evidence for secondary structure. A linear tetramer was cyclised to a 28-membered ring lactam in modest yield, which on deprotection formed a class of macrocycle with structural features of both a cyclic peptide and a cyclodextrin. © 2004 Elsevier Ltd. All rights reserved.